Clinical implications of the titer of serum hepatitis B surface antigen during the natural history of hepatitis B virus infection. Issue 1 (30th September 2013) - Suh, Sang Jun; Bae, Song‐I; Kim, Ji Hoon; Kang, Keunhee; Yeon, Jong Eun; Byun, Kwan Soo
Abstract Although there are some differences in hepatitis B surface antigen (HBsAg) titers in infection with different hepatitis B virus (HBV) genotypes, the HBsAg titers for each HBV genotype have not been evaluated extensively. The aim of this study was to investigate HBsAg titers during the natural history of patients infected with HBV in Korea, where the HBV genotype C is endemic exclusively. Four hundred fifteen patients were enrolled retrospectively and classified according to definitions of the natural phases of HBV infection. In total, 73, 118, 147, and 77 patients were classified in the immune tolerance, immune clearance, low replicative, and HBeAg‐negative hepatitis phases, respectively. HBsAg titers (4.35 ± 0.67, 3.74 ± 0.68, 2.39 ± 1.23, and 3.29 ± 0.64 log10 IU/ml) were significantly different in the immune tolerance, immune clearance, low replicative, and HBeAg‐negative hepatitis phases, respectively (P < 0.001). The ratio of HBsAg to HBV DNA was highest in the low replicative phase (1.13 ± 0.71, all P < 0.001) and second highest in the HBeAg‐negative hepatitis phase (0.58 ± 0.18, all P < 0.05). In multivariate analysis of all patients, the HBsAg titers did not correlate with alanine aminotransferase. However, the HBsAg titers correlated with age (P = 0.038), platelet count (P < 0.001) and HBV DNA (P < 0.001). In subgroup analysis, the HBsAg titers correlated with HBV DNA in all phases (P < 0.001), except for the HBeAg‐negative hepatitis phase. HBsAg titers were significantly different across the four phases of the natural history of the infection and correlated significantly with HBV DNA titer in genotype C chronic hepatitis B patients. The HBsAg titer could be used as a biomarker to differentiate the natural history of HBV infection. J. Med. Virol. 86:117–123, 2014. © 2013 Wiley Periodicals, Inc.